2021
DOI: 10.1177/1362361320982819
|View full text |Cite
|
Sign up to set email alerts
|

Health characteristics of reproductive-aged autistic women in Ontario: A population-based, cross-sectional study

Abstract: While an increasing number of girls and women are being identified with autism, we know little about the health of reproductive-aged autistic women. Our objectives were to (1) describe health characteristics of reproductive-aged autistic women who could potentially become pregnant and (2) compare these characteristics with those of non-autistic women. We conducted a population-based cross-sectional study using 2017–2018 administrative health data from Ontario, Canada. A total of 6,870 fifteen- to 44-year-old a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The present study fills current knowledge gaps as the findings are derived from a large, population-based sample of autistic women and men matched by age with adults with other DD and those without DD. Echoing a growing number of administrative data studies from other jurisdictions (Cawthorpe, 2017;Croen et al, 2015;Davignon et al, 2018;Hand et al, 2019;Smith DaWalt et al, 2021;Tint et al, 2021), we found that autistic women and men were more likely to have a wide variety of physical and mental health conditions and to use health services more compared to women and men without DD. There were some significant sex differences for specific physical (i.e.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The present study fills current knowledge gaps as the findings are derived from a large, population-based sample of autistic women and men matched by age with adults with other DD and those without DD. Echoing a growing number of administrative data studies from other jurisdictions (Cawthorpe, 2017;Croen et al, 2015;Davignon et al, 2018;Hand et al, 2019;Smith DaWalt et al, 2021;Tint et al, 2021), we found that autistic women and men were more likely to have a wide variety of physical and mental health conditions and to use health services more compared to women and men without DD. There were some significant sex differences for specific physical (i.e.…”
Section: Discussionmentioning
confidence: 79%
“…A small but steadily increasing number of studies using administrative data demonstrate that autistic adults have elevated physical health and psychiatric conditions (Cawthorpe, 2017;Chiang et al, 2015;Croen et al, 2015;Davignon et al, 2018;Hand et al, 2019;Kohane et al, 2012;Schott et al, 2022aSchott et al, , 2022bSmith DaWalt et al, 2021;Tint et al, 2021;Tyler et al, 2011;Vohra et al, 2017;Weiss et al, 2018) and higher health service use rates (Ames et al, 2021;Hand et al, 2018;Smith DaWalt et al, 2021;Vohra et al, 2016Vohra et al, , 2017Weiss et al, 2018;Zerbo et al, 2019) compared to the general population. The majority of these studies, however, are comprised predominantly of young adult males (Cawthorpe, 2017;Chiang et al, 2015;Davignon et al, 2018;Kohane et al, 2012;Tyler et al, 2011;Weiss et al, 2018) and many do not include sex-stratified analyses to allow for an understanding of autistic women's patterns of need.…”
mentioning
confidence: 99%
“…The use of cross‐sectional data also precludes causal inference or temporal sequence between the variables (Wang & Cheng, 2020). The generalizability of the findings may be limited by the specific characteristics of the study population and setting (Tint et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Autistic individuals were identified when autism diagnoses were recorded at 2 or more outpatient physician visits, 1 or more emergency department visit or same-day surgery, or 1 or more hospitalization, using codes from the International Classification of Diseases, Ninth Revision (code 299), International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10) (codes F84.0, F84.1, F84.3, F84.5, F84.8, and F84.9), or Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) (code 299), as a fixed-effect variable. This previously used algorithm 28 has excellent specificity and moderate sensitivity. 29 For self-harm events and suicide death we had different accrual and follow-up periods owing to data availability (see Outcome Measures).…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%